(untitled) (Trabalho & Educação, 2016)
A doctoral research activity approached the problem of the relationship between work and mental health from ergological notions of use of oneself and symptom of psychoanalysis. In this thesis I present a reading of the symptom as use of oneself seeking recognize both the social causes of symptoms (the use of oneself by others) as the action strategy on this same determination (in the use of oneself by oneself their ever-present). What I advocate in this thesis is that a clinical course of the relationship between work and mental health at the same psychoanalytic and ergological time, can happen by listening to the use that each individual makes of himself with his symptom, what is at stake in every activity (work). The embarrassment I seek worked in this essay is, in this view takes in some way, the historical chain of activities in my life? As these activities have led me to this research question and why paths sought the answers? This is what I will try to explain not questioning the neutrality of the research object and how it fits on a specific personal journey. ___ Numa atividade de pesquisa do doutorado, abordei o problema da relação entre trabalho e saúde mental a partir das noções ergológica de “uso de si” e psicanalítica de “sintoma”. Na tese, apresentei uma leitura do sintoma como uso de si buscando reconhecer tanto a determinação social dos sintomas (o uso de si pelos outros) quanto a estratégia de ação sobre essa mesma determinação (no uso de si por si, sempre presente). O que defendo na tese é que uma condução clínica da relação entre trabalho e saúde mental, ao mesmo tempo psicanalítica e ergológica, pode se dar pela escuta do uso que cada sujeito faz de si com seu sintoma, o que está em jogo em toda atividade (trabalho). O embaraço que busco, trabalhado neste ensaio, é: no que essa tese retoma, de alguma forma, o encadeamento histórico das atividades realizadas durante minha vida? Como essas atividades me levaram a tal questão de pesquisa e por que caminhos busquei as respostas? É o que tentarei explicitar problematizando a não neutralidade do objeto da pesquisa e o modo como ele se inscreve em um percurso pessoal específico.